2018
DOI: 10.17681/hsp.422360
|View full text |Cite
|
Sign up to set email alerts
|

Doğum Yapan Kadınların Doğumdan Memnuniyeti ve Etkileyen Faktörler

Abstract: Bu çalışma; doğum yapan kadınların doğumdan memnuniyet düzeyleri ve etkileyen faktörleri belirlemek amacıyla yapılmıştır. Gereç ve Yöntem: Çalışma kesitsel ve tanımlayıcı tiptedir. Araştırma Bolu ilinde bir devlet hastanesinde doğum yapan primipar ve multipar 387 kadın ile yürütülmüştür. Veriler anket formu ile toplanmıştır. Verilerin değerlendirilmesinde tanımlayıcı istatistiksel metodlar, bağımsız gruplarda t testi, ki kare testi, One Way Anova ve Pearson korelasyon testi kullanılmıştır. Bulgular: Kadınların… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 23 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Since the average maternal satisfaction scores were below the cut-off point, the satisfaction level was found to decrease 100% (Table 5). In the studies by Çapık et al (13) and Çıtak Bilgin et al (21) , it was found that the women who gave vaginal birth were more satisfied with the mode of birth. Our study did not show parallelism with the studies by Çapık et al (13) and Çıtak Bilgin and et al (21) .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Since the average maternal satisfaction scores were below the cut-off point, the satisfaction level was found to decrease 100% (Table 5). In the studies by Çapık et al (13) and Çıtak Bilgin et al (21) , it was found that the women who gave vaginal birth were more satisfied with the mode of birth. Our study did not show parallelism with the studies by Çapık et al (13) and Çıtak Bilgin and et al (21) .…”
Section: Discussionmentioning
confidence: 97%
“…In the studies by Çapık et al (13) and Çıtak Bilgin et al (21) , it was found that the women who gave vaginal birth were more satisfied with the mode of birth. Our study did not show parallelism with the studies by Çapık et al (13) and Çıtak Bilgin and et al (21) . In our study, it was suggested that the satisfaction level was affected by other factors than mode of birth.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[17] In a study conducted at a state hospital, 50.4% of mothers were found to give vaginal birth and 80% of them gave birth with episiotomy. [18] In a study conducted at a maternity hospital, 40.5% of mothers were found to give vaginal birth and 29.7% of them gave birth with episiotomy. [6] In Turkey, while caserean section rate was 53.1% in the same year, vaginal childbirth rate was higher in the study when compared to literature.…”
Section: Discussionmentioning
confidence: 99%